1998
DOI: 10.1136/jmg.35.2.153
|View full text |Cite
|
Sign up to set email alerts
|

A patient with Simpson-Golabi-Behmel syndrome and hepatocellular carcinoma.

Abstract: Simpson-Golabi-Behmel syndrome (SGBS) is an X linked disorder characterised by pre-and postnatal overgrowth, coarse facial features, and visceral and skeletal abnormalities. Like other overgrowth syndromes, in the SGBS there is an increased risk for developing neoplasia, mainly embryonic, such as Wilms tumour. We report a 3 year old male patient with SGBS and hepatocellular carcinoma, a previously undescribed tumour associated with the syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Although the number of patients with M-CMTC currently reported is low, and the types of neoplasia seen so far are heterogeneous, the putative 5-6% tumor risk is similar to that of overgrowth syndromes [Cohen, 1989;Lapunzina et al, 1998Lapunzina et al, , 1999Cohen et al, 2002]. Thus, as recommended recently, this syndrome deserves tumor screening until more patients are described and evaluated to clarify the risk of neoplasia [Lapunzina, 2004] (in press).…”
Section: Tumorsmentioning
confidence: 82%
“…Although the number of patients with M-CMTC currently reported is low, and the types of neoplasia seen so far are heterogeneous, the putative 5-6% tumor risk is similar to that of overgrowth syndromes [Cohen, 1989;Lapunzina et al, 1998Lapunzina et al, , 1999Cohen et al, 2002]. Thus, as recommended recently, this syndrome deserves tumor screening until more patients are described and evaluated to clarify the risk of neoplasia [Lapunzina, 2004] (in press).…”
Section: Tumorsmentioning
confidence: 82%
“…1) (four Wilms tumors, two hepatoblastomas, one adrenal neuroblastoma, one gonadoblastoma, and one hepatocellular carcinoma Li et al, 2001]. Cases reported by Harrod and Kettman, 1992;Hughes-Benzie et al, 1996;Pilia et al, 1996;Lindsay et al, 1997;Lapunzina et al, 1998;Li et al, 2001. a One case of hepatoblastoma Lapunzina, personal observation; not published.…”
Section: Simpson-golabi-behmel Syndromementioning
confidence: 93%
“…Probably not increased -Perlman syndrome 30%-40% 1:2.5 (Â2700) Henneveld et al, 1999;Lapunzina et al, 2001 Simpson-Golabi-Behmel syndrome $7.5% (5%-10%) 1:10 (Â600) Lapunzina et al, 1998;Lin et al, 1999 Sotos syndrome $4% (2.3%-5%) 1:40 (Â150) Cohen, 1989;Hersh et al, 1992;Jones, 1994;Weaver, 1994 Weaver syndrome 1:25 (Â200) Hoyme et al, 1986Hoyme et al, , 1998 Proteus syndrome…”
Section: Ndamentioning
confidence: 96%
“…Cerebral malformations have been also reported in several cases of SGBS, though it has been impossible to prove the existence of GPC3 expression in the brain, with the exception of the infundibular recessus and the diencephalon [Pellegrini et al, 1998]. Abnormal corpus callosum (agenesis, hypoplasia, or lipomas) was reported by several authors [Le Merrer et al, 1989;Chen et al, 1993;Lapunzina et al, 1998], and all three patients reported by Le Merrer et al [1989] also had brain malformations. Our patient IV-10 showed corpus callosum agenesis, but his severe neurological impairment could well be the result of perinatal hypoxia due to his dramatic perinatal period.…”
Section: Discussionmentioning
confidence: 83%
“…The most consistent findings in SGBS are pre-and postnatal overgrowth, ''coarse'' face, macrostomia and macroglosia, a midline groove of the lower lip and/or tongue, and other anomalies affecting the internal organs and bones [Opitz et al, 1988]. SGBS is also associated with an increased risk of developing embryonal tumors, mostly of the kidneys and liver [Hughes-Benzie et al, 1992;Lapunzina et al, 1998;Lapunzina, 2005]. Xuan et al [1994] mapped the gene responsible for SGBS to Xq25-q27 and in the same year, Orth et al [1994] further refined the mapping near HPRT in Xq26.…”
Section: Introductionmentioning
confidence: 93%